2018
DOI: 10.1016/j.ajme.2017.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of methylenetetrahydrofolate reductase (MTHFR) A1298C gene polymorphism on the outcome of methotrexate treatment in a sample of Egyptian rheumatoid arthritis patients

Abstract: Background: Methotrexate is the most commonly used disease-modifying anti-rheumatic drug (DMARD) and it is considered the first-line treatment in the management of rheumatoid arthritis (RA). MTX treatment outcome regarding response to the drug and adverse effects in RA patients are not universal. Therefore, it would be beneficial if we could predict the response of patients to MTX before starting MTX treatment in order to determine the patient ' s drug-treatment plan. Objectives: The present study aimed to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
(28 reference statements)
0
6
1
Order By: Relevance
“…[19] Patients were divided into 2 groups, in which the responder group was defined as (disease activity score) DAS28 ≤ 3.2, and non-responder DAS28 > 3.2 after at least 3 months of MTX treatment (tablet or parenteral formulations), one reading of DAS28 used to calculate treatment response. [20][21][22] Responder groups included 47 patients and 48 patients as non-responders.…”
Section: Methodsmentioning
confidence: 99%
“…[19] Patients were divided into 2 groups, in which the responder group was defined as (disease activity score) DAS28 ≤ 3.2, and non-responder DAS28 > 3.2 after at least 3 months of MTX treatment (tablet or parenteral formulations), one reading of DAS28 used to calculate treatment response. [20][21][22] Responder groups included 47 patients and 48 patients as non-responders.…”
Section: Methodsmentioning
confidence: 99%
“…Patients were divided into two groups according to a previous study 24 , in which the responder group was defined as DAS28 ≤ 3.2, and the nonresponder DAS28 > 3.2 after at least three months of MTX treatment 24 26 . Responder groups included 48 patients and 47 patients as nonresponders.…”
Section: Methodsmentioning
confidence: 99%
“…One of the studies done in Indian subjects by Ghodke Puranik et al; explained that RA patients with one dominant Aallele at least (AA or AC of A1298C genotypes) could benefit from MTX treatment when compared with those who have the homozygous recessive genotype CC [29]. On the other hand, Shakari et al showed that homozygous recessive genotype CC and heterozygous genotype AC has a significant association with not responding to MTX drug (p <0.05), and RA patient who were carrying recessive allele C has significant association with not responding to MTX (p <0.05) [18]. In contrast to our result, Grabar et al did not detect any significant association between MTX response and MTHFR A1298C genotypes [33].…”
Section: The Relation Between Mthfr Polymorphisms and Mtx Outcomes (M...mentioning
confidence: 99%
“…The single SNPs of MTHFR were associated with MTX outcomes in RA. Nevertheless, the results of these studies are controversial and inconclusive [17][18].…”
Section: Introductionmentioning
confidence: 99%